An eco-psychological framework for research on the physical environment of childcare classrooms and children’s play behavior - Deng, Chenhao; Zhao, Zhiyi; Ahmad Noorhani, Nur maizura; Mustapha, Arniatul Aiza (Frontiers in Psychology, 2024)
Ecological psychology is an approach focus on the perception and behavior of organisms and environments, offering psychological insights for research on children. This study primarily explores the concepts of affordance and behavior setting based on eco-psychological perspective concerning children’s behaviors and environment. Through a review of previous studies, differentiated that affordance theory emphasizes children’s direct perceptions of environmental functions, whereas the concept of behavior setting highlights the dyadic relationship between long-term behaviors and environmental material features. However, existing studies on child-environment interactions often overlook children’s immediate actions in the context of affordance theory and fail to account for the dynamic nature of behavior settings. by integrating the distinctive traits of both theories, this study proposes an anticipatory framework based on ecological psychology to guide research on children’s environments, particularly within the indoor spaces of childcare facilities. Future studies should investigate the connections within this framework through field studies of childcare center environments and observations of children’s actions and behaviors during free play to assess congruence with environmental affordances.